Dig deeper – insights into the genetic, physiological and climatic implications of deep root architecture of rice plants - Tiwary, Raghuvar; Chettri, Upashna; Hasnu, Chetana; Borah, Pratikshya (Frontiers in Plant Physiology, 2025)
Rice (Oryza sativa L.) is a basic staple crop, sustaining nearly half of the global population and underpinning the livelihoods of millions. As climate change exacerbates the frequency of drought, salinity, and nutrient limitations, optimizing rice root system architecture (RSA)—particularly deep root systems—has become essential for ensuring productivity and resilience. Deep RSA, characterized by steeper root growth angles and extensive large lateral roots, enhances access to water and nutrients in deeper soil layers, improving drought tolerance, nutrient use efficiency, and yield stability under environmental stress. This review synthesizes advances in understanding the physiological, genetic, and hormonal regulation of deep root development in rice. Key genes, including DEEPER ROOTING 1 (DRO1), qSOR1, and SOR1, regulate root growth angle and depth, while aquaporins and hormonal pathways (auxin, cytokinin, ethylene, abscisic acid, gibberellin) modulate root dynamics and water transport. The plasticity of RSA allows rice to adapt to diverse environments, with deeper roots conferring resilience to drought and nutrient deficiency, and shallower roots offering advantages in saline soils. Advances in marker-assisted selection, genome editing (CRISPR-Cas9), and RNA-based technologies enable precise manipulation of root traits, accelerating the development of climate-resilient rice varieties. Agronomic practices such as deep fertilizer placement further promote rooting depth and resource use efficiency. Additionally, deep RSA offers potential as a sustainable carbon sink, contributing to climate change mitigation. By leveraging these innovations, deep root systems can enhance rice crop resilience and support sustainable agriculture, ensuring global food security in a changing climate.